Schedule performance of express train services. a case study of KTM Berhad / Suhaila Ibrahim - Ibrahim, Suhaila (1995)
For more than a century, Keretapi Tanah Melayu has help the nation meets its economic and social objectives. Today, as it becomes a commercial entity, KTM Berhad is embarking on an era of dynamic change. All indications point to it becoming a vibrant transport operator scoring impressive gains over other modes of transport in Malaysia's highly competitive sector. Judging from the current trends, the demand for rail transportation is projected to increase tremendously. There will be massive changes, both structurally as well as physically, because privatisation means new function, a fresh identity and positive culture. The strong economic growth , a rising demand for both freight and passenger transportation coupled with congestion found in other forms of transportation, opens the way for rail as the industrialised world. KTM Berhad is fully aware of the significant role it must play in assisting the government realise its mission of making Malaysia a fully industrialised nation by the year 2020. KTM Berhad is embarking on a route leading to financial health and renewed public image. KTM Berhad will strive for quality and excellence in all areas of activities, both for external public as well as for internal stockholders. A new era in railroad transportation has begin, with privatisation to act as a momentum in moving Malaysia ahead.